Disease-beating banana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Black sigatoka and Panama disease are the two worst fungal diseases to afflict bananas. But a new variety of banana developed at the Honduran Foundation for Agricultural Research (HFRA) is much hardier than traditional varieties and is resistant to...